Coping strategies related to treatment in substance use disorder patients with and without comorbid depression - Adan, Ana; Antúnez-Vílchez, Juan Manuel; Navarro-Humanes, José Francisco (Elsevier, 2017)
Coping strategies exert an important influence in the development and course of both substance use disorder (SUD) and major depressive disorder (MDD) and its treatment outcomes. We examined the coping strategies related to treatment in SUD and SUD-MDD patients and their associations with clinical characteristics. Forty SUD and 40 SUD-MDD males, each group composed by 20 therapeutic community and 20 ambulatory treatment patients, were assessed through the Coping Strategies Inventory and clinical characteristics questionnaires. SUD-MDD patients scored higher in Disengagement strategies such as Social Withdrawal and lower in Engagement ones such as Problem Solving, Cognitive Restructuring and Social Support, as well as in self-perceived capacity for coping. No differences for treatment were found. SUD and, specially, SUD-MDD patients scored higher than norms in maladaptive strategies. Time of abstinence, age of onset and severity of SUD were related to maladaptive coping. SUD and SUD-MDD patients are prone to employ Disengagement coping strategies and SUD-MDD patients coping repertory is more maladaptive than the SUD ones. Likewise, clinical characteristics associated to maladaptive coping might differ by diagnosis and modality of treatment in male patients. These findings could be considered for the treatment design and to improve the recovery and prevent relapses.
Keywords: Depresión mental - Tratamiento; Coping strategies; Dual diagnosis; Major depressive disorder; Substance use disorder; Treatment modality